A lattice defect-inspired leaching strategy toward simultaneous recovery and separation of value metals from spent cathode materials. (November 2021) - Tao, Hongbiao; Yang, Yue; Xu, Shengming; Liu, Qi; Huang, Guoyong; Xu, Zhenghe
Highlights: A selective leaching technique has been invented. The feasibility of this technique was first demonstrated. A spent LiNi1/3 Co1/3 Mn1/3 O2 material was recycled without a separation step. Abstract: Efficient recycling of high-value metals from spent cathode materials is important in that it not only alleviates the severe shortage of raw material supply but also addresses the environmental and safety issues associated with the disposal of these materials. Here, we report a selective leaching strategy by virtue of the defect-induced lattice instability. In contrast to the traditional "primary leaching – multistep separation" process, this technique enables simultaneous recovery and separation of value metals from the waste cathode by selective dissolution. The feasibility of this technique was first demonstrated by density functional theory (DFT) calculations, and then confirmed by laboratory studies in which a spent LiNi1/3 Co1/3 Mn1/3 O2 material was successfully recycled, where the recoveries of Li, Ni/Co and Mn reached close to 100%, 99.5%/98.2% and 100%, respectively, without the need for a separation step. The recovery of Li, Ni/Co and Mn uses oxalic acid, phosphoric acid and sulfuric acid as leaching agents, respectively. We believe that this work has both practical and theoretical significance, in that the strategy has the potential to be expanded to the recovery/recycling of many other spent materials, and that the atomic-scale insight on the relation between vacancies and lattice stability offers new perspective for developing advanced recycling strategies.